A new species of Begonia L. (Begoniaceae) and some notes on Begonia difformis from Kachin, northern Myanmar - Wahlsteen, Eric (Phytotaxa, 2019)
The new species Begonia dicressine (sp. nov.) belonging to Begonia section Platycentrum is described. The new species is similar to B. rockii but differs in having petioles with long soft white hairs, plain dark green leaves with irregularly crenate margins, lower surface only with appressed hairs along midrib, and glabrous inflorescences. B. dicressine is distributed in Kachin Province in northern Myanmar in the understory of evergreen and semi-deciduous forests. New records of B. difformis from the same area are also reported, and its distribution and habitat are discussed.